Informal learning at school. Science fairs in basic schools - Esteves, Zita (2008)
The communication herein reports on the second edition of the annual Science Fair at Externato Maria Auxiliadora, in Viana do Castelo, Portugal. It was intended to give continuity to the research project on science fairs of the previous year improving, based on past conclusions, some aspects: the age group of the participants was enlarged to ages 10 to 15, and there was a major effort to engage parents and the whole school community in the process and in the development/construction of the projects to the science fair. Besides that, to the teachers involved in the project, was assigned an increased set of weekly hours to give support to the works realization. The participation of the students was not obligatory and it had no weight in the student’s formal evaluation. The results suggested that the whole school benefited from the enlargement of the age group of the participants in the event, and that the projects made by the younger students were particularly interesting. We concluded again that the Science Fair contributed effectively to an increase of the student’s interest on scientific subjects.